Financial incentive schemes in primary care - Gillam S (Dove Medical Press, 2015)
Stephen Gillam Department of Public Health and Primary Care, Institute of Public Health, University of Cambridge, Cambridge, UK Abstract: Pay-for-performance (P4P) schemes have become increasingly common in primary care, and this article reviews their impact. It is based primarily on existing systematic reviews. The evidence suggests that P4P schemes can change health professionals' behavior and improve recorded disease management of those clinical processes that are incentivized. P4P may narrow inequalities in performance comparing deprived with nondeprived areas. However, such schemes have unintended consequences. Whether P4P improves the patient experience, the outcomes of care or population health is less clear. These practical uncertainties mirror the ethical concerns of many clinicians that a reductionist approach to managing markers of chronic disease runs counter to the humanitarian values of family practice. The variation in P4P schemes between countries reflects different historical and organizational contexts. With so much uncertainty regarding the effects of P4P, policy makers are well advised to proceed carefully with the implementation of such schemes until and unless clearer evidence for their cost–benefit emerges. Keywords: financial incentives, pay for performance, quality improvement, primary care